Understanding Identity and Disability in the Middle-grade Novel Caleb and Kit by Beth Vrabel - Aura Annisa; Harwintha Yuhria Anjarningsih (Universitas Sanata Dharma, 2025)
Children’s literature has long been associated with key ideologies and morals for children. Through literary themes, children will learn how to perceive themselves and their surroundings. Beth Vrabel’s book Caleb and Kit (2017), which features Caleb as a kid with cystic fibrosis, explores identity and disability, two important themes in this children’s literature. These two important themes are analysed using Critical Discourse Analysis (CDA) with critical sociocultural approach by Moje and Lewis (2007) to examine identity in literature and disability model’s framework to analyse disability representations and the relation to the protagonist’s identity. This study portrays a child's experience with disability by examining the main character's words, actions, and interactions, revealing how both condition and environment alter identity and relationships throughout time. The study finds that the portrayal of disability is multidimensional, shifting as the narrative progresses, emphasizing the dynamic aspect of the character's experiences. Two popular disability models, medical and social, are utilized to investigate the various aspects of disability experience, as reflected in the characters and narrative. Long-standing criticisms of these two paradigms are included in the story, impacting how the characters see disability. This study suggests that both disability models operate best when used together as a full framework for critically analyzing the constructions of disability identity in children's literature and assisting the reader in understanding this issue in their surroundings.